Advances in Stereotactic and Functional Neurosurgery 9 Proceedings of the 9th Meeting of the European Society for Stereotactic and Functional Neurosurgery, Malaga 1990 - Hitchcock, Edward R.; Broggi, Giovanni; Burzaco, Juan; Martin-Rodriguez, J. (Advances in Stereotactic and Functional Neurosurgery, 1991)
The book gives the most up-to-date information for the expanding field of stereotactic and functional neurosurgery from European and international experts. The newest developments in neural transplantation and stereotactic irradiation are included together with the reports on extensive trials of analgesic surgery and new techniques used in the treatment of a variety of functional disorders